2017
DOI: 10.1038/srep45583
|View full text |Cite
|
Sign up to set email alerts
|

Corrugated Textile based Triboelectric Generator for Wearable Energy Harvesting

Abstract: Triboelectric energy harvesting has been applied to various fields, from large-scale power generation to small electronics. Triboelectric energy is generated when certain materials come into frictional contact, e.g., static electricity from rubbing a shoe on a carpet. In particular, textile-based triboelectric energy-harvesting technologies are one of the most promising approaches because they are not only flexible, light, and comfortable but also wearable. Most previous textile-based triboelectric generators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…A good example of T-TENG, which can operate in a lateral stretching and release mode was reported by Choi et al They designed a T-TENG with a corrugated structure, shown in Fig. 11(a) [99]. The top layer was produced by backstitching silk with a woven conductive fabric (Sn/Cu/Ag-plated nylon).…”
Section: Fabric-based T-teng Using the Fabric As Triboelectric Layermentioning
confidence: 99%
See 1 more Smart Citation
“…A good example of T-TENG, which can operate in a lateral stretching and release mode was reported by Choi et al They designed a T-TENG with a corrugated structure, shown in Fig. 11(a) [99]. The top layer was produced by backstitching silk with a woven conductive fabric (Sn/Cu/Ag-plated nylon).…”
Section: Fabric-based T-teng Using the Fabric As Triboelectric Layermentioning
confidence: 99%
“…In the case of fabric-based T-TENGs, thin layers of flexible materials can be used to realize the TENG without affecting the mechanical properties of the textile [111]. Thanks to the nature of textile structures, most T-TENGs are therefore inherently flexible and some of them are stretchable [41,81,99]. One challenge of T-TENGs is that their appearance is often not aesthetically pleasing since the applied coatings will alter the appearance of the fabric.…”
Section: Multiple-thread Fully-integrated T-tengmentioning
confidence: 99%
“…Wearable smart textiles incorporate electroactive materials (EAMs) that allow the conversion of mechanical energy to electrical energy and vice versa 26. The motion of the body can serve as the mechanical energy required for the energy conversion.…”
Section: Advances In Wearable Devicesmentioning
confidence: 99%
“…A considerable volume of papers has been published since its inception in 2012 26, 29, 93, 94, 95, 96, 97, 98, 99. Recently, fiber type TENGs have been reported with flexible, soft, breathable, and wearable characteristics suitable for energy generation and integration into textiles 26, 100, 101…”
Section: Fiber‐shaped Energy Harvesting Devicesmentioning
confidence: 99%
See 1 more Smart Citation